Love for family, friends, and books - Ziolkowska-Boehm, Aleksandra, 1949- (Hamilton Books, 2015)
"An autobiography unlike other literary forms shows the ego of an author. Aleksandra Ziolkowska-Boehm's ego is delicate, fascinating, and courageous. Some fragments are almost like a movie with interesting dialog, compelling moments, and realistic characters. Vividly portrayed are dedicated and devoted parents who instilled a love for reading and books that formed the foundation for her career. Detailed descriptions of coping with the rigors of achieving an advanced education, career start, and caring, rearing and devoting love to a young son are outstanding."--